INFLUENCE INTELLECTUAL CAPITAL ABOUT COMPANY VALUE IN MANUFACTURING COMPANIES IN BASIC AND CHEMICAL INDUSTRY SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2019 – 2021 - Saputri, Irma Aullia; Widyawati (Indragiri Research Center (ingreat), 2023)
This research was conducted at Manufacturing companies in the Basic Industry and Chemical Sector which are listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This study aims to determine the effect of Intellectual Capital on Firm Value. The population of the research conducted by the researcher was 78 Manufacturing Companies in the Basic Industry and Chemical Sector with a sample of 12 companies with a period of 3 years with a total of 36 companies. Analysis of the data in this study used the classical assumption test and Simple Linear Regression Analysis as an analysis tool that was processed with IBM SPSS 23 Software. The results of the analysis proved that the Coefficient of Determination test (R²) obtained a result of 0.316 or 31.6%, this indicates that the variable (VAIC™) on the dependent variable Firm Value of 31.6%, while the remaining 69.4% is influenced by other variables not included in this study. From the results of the Simple Linear Test, the regression equation is obtained, namely: Y = (-530.964) + 259.169X. The results of the partial T-test study variable value added intellectual coefficient (VAIC™) (X₁) tcount 3.959>ttable (1.691), and a sig value of 0.000 <0.05, indicating that VAIC™ has a significant effect on firm value (Y). Significant Manufacturing Companies in the Basic Industry and Chemical Sector Listed on the Indonesia Stock Exchange for the 2019-2021 period.